Process Optimization Using RPA as an Element of change Management in the Organization - Paula Pypłacz; Janusz Sasak (Perspektywy Kultury, 2023)
Robotic Process Automation (RPA) technology is being used more and more often in small and medium enterprises. This tool is becoming increasingly important in relieving workers from time consuming and boring tasks. The aim of the research was to identify current problems encountered by enterprises when implementing RPA solutions, with particular attention paid to the aspect of change perceived by the employees and the management. As part of the empirical work, monographic research was conducted using the case study procedure in 10 selected small and medium-sized companies operating in Poland. During expert interviews, workers’ resistance against changes was noticed as the greatest obstacle in introducing RPA. Workers’ lack of knowledge about this technology and its tools and the lack of proper change management in organizations are the main factors which impede implementation of RPA. The core actions to success in implementation of software robots are: building awareness among workers, support of leaders, and monitoring of implementation progress.